2020
DOI: 10.1007/s00787-019-01467-6
|View full text |Cite
|
Sign up to set email alerts
|

Training for child and adolescent psychiatry in the twenty-first century

Abstract: We are a relatively young medical specialty and have found our roots in the past century in a combination of medicine (adult psychiatry and pediatrics), psychology and cooperation with various professionals involved with child/youth care and education. These historical origins are reflected in our activities today and we have witnessed a growth in number of both child and adolescent psychiatrists and trainees over the past decades. At the same time, there has also been a tremendous increase in demand for child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…There are newly emerging networks of international information exchange about the effects of Corona on mental health and to share lessons learned. The further development of an international network of CAP trainers as well as the development of courses on an international level and MOOCs may prove to be crucial to maintain training [6]. After the crisis, it will be important to avoid delays in training caused by the crisis.…”
mentioning
confidence: 99%
“…There are newly emerging networks of international information exchange about the effects of Corona on mental health and to share lessons learned. The further development of an international network of CAP trainers as well as the development of courses on an international level and MOOCs may prove to be crucial to maintain training [6]. After the crisis, it will be important to avoid delays in training caused by the crisis.…”
mentioning
confidence: 99%
“…An interest in psychotherapy, both as a professional practice and a personal experience, contrasts with the lack of official training provided during residency and the high level of heterogeneity in personal training offering, which depends heavily on the region and the university hospitals throughout France. This is especially problematic with regard to the diversity of psychotherapy approaches used in CAP, from cognitive–behavioral therapy to psychanalysis, and the time required to acquire skills and experience ( 20 ). Interestingly, an online survey ( 40 ) conducted in psychiatric trainees from 22 countries found that the risk of severe burnout was higher in psychiatric trainees who had not opted for psychiatry as a first career choice.…”
Section: Discussionmentioning
confidence: 99%
“…Child and adolescent psychiatrists need the competencies to deal with complex disorders that have their origins in the biological, psychological, systemic, contextual, and cultural domains ( 20 ). This level of complexity, as well as the lack of familiarity of medical students with this type of bio-psycho-social approach, may explain this apparent lack of attractiveness of CAP.…”
Section: Introductionmentioning
confidence: 99%
“…An array of alternative services and treatments is needed, ranging from interventions targeting at-risk youth and families before patterns of maladaptive behaviors become entrenched, to more intensive community-based services (e.g., intensive outpatient, mobile response and stabilization services, partial hospitalization) for youth suffering from chronic mood and behavioral dysregulation, and unsafe behaviors (the current high utilizers within the system). Workforce and training priorities also need to be addressed, with the focus on developing clinicians capable of, and willing to provide effective evidence-based pharmacologic, behavioral, and psychosocial treatments (Deschamps et al, 2020). We should pay for what works.…”
mentioning
confidence: 99%